Mathematical aspects of various methods for sampling from classical distributions - Dieter, U. (Proceedings of the 21st conference on Winter simulation, 1989)
Simulations were one of the first subjects J.v. Neumann had in mind for applying computers. He recom- mended some methods for generating [0,1)-uniformly distributed random numbers which are out of use today. However, his ideas for sampling from non-uniform distributions are still widely used. Since his 1951-paper is rather short, improvements and generalisations of his ideas have been found in the meantime. They will be discussed in this paper.